Numerical Simulation of Fractional Fornberg-Whitham Equation by Differential Transformation Method - Mehmet Merdan; Ahmet Gökdogan; Ahmet Yıldırım; Syed Tauseef Mohyud-Din (Abstract and Applied Analysis)
An approximate analytical solution of fractional Fornberg-Whitham equation was obtained with the help of the two-dimensional differential transformation method (DTM). It is indicated that the solutions obtained by the two-dimensional DTM are reliable and present an effective method for strongly nonlinear partial equations. Exact solutions can also be obtained from the known forms of the series solutions.